Pattern of Bacterial Pathogens Causing Urinary Tract Infection and Their Antibiotic Sensitivity: A Tertiary Care Hospital Experience - Rahman, Raziur; Rahim, Muhammad Abdur; Afroze, Samira Rahat; Mitra, Palash; Samad, Tabassum; Tareqe, Ashfaqe; Ahmed, Jamal Uddin; Musa, AKM; Afroz, Farhana; Haque, Hasna Fahmima; Ananna, Mehruba Alam; Ahmed, AKM Shaheen; et al. (BIRDEM Medical Journal, 2016)
Background and Aims: Urinary tract infection (UTI) is a common illness. The spectrum of bacteria causing UTI and their antibiotic sensitivity is not uniform. This study was designed to describe the bacteriological spectrum causing UTI and their antibiotic sensitivity. Methods: This cross-sectional study was done in the Department of Internal Medicine, BIRDEM General Hospital from January to June, 2013. Results: Total number of patients was 103 with females predominance (F:M ratio 2:1). Mean age was 57.5 years. Most (91.3%) of the study population were diabetic with poor glycaemic control (mean HbA1c 9.9%). Common symptoms were fever, dysuria, increased urinary frequency, suprapubic pain, vomiting and loin pain. Neutrophilic leukocytosis was common (94.2%). E. coli (79.6%) was the commonest aetiological agent followed by Klebsiella (9.7%), Citrobacter (3.9%), Acinetobacter (1.9%), Enterobacter (1.9%), Enterococcus (1.9%) and Pseudomonas (0.9%). Imipenem (100%), aminoglycosides e.g. amikacin and gentamycin and nitrofurantoin were among the most sensitive antibiotics. Conclusion: E. coli is the commonest organism causing UTI and imipenem, amikacin and nitrofurantoin are the most sensitive antibiotics. Birdem Med J 2015; 5(1): 20-23